Classification of distinct tendinopathy subtypes for precision therapeutics - Chenqi Tang; Zetao Wang; Yuanhao Xie; Yang Fei; Junchao Luo; Canlong Wang; Yue Ying; Peiwen He; Ruojing Yan; Yangwu Chen; Jiayun Huang; Yiwen Xu; et al. (Nature Communications)
Abstract Rotator cuff tendinopathy is the most common tendinopathy type with the worst prognosis. Conventional treatments often elicit heterogeneous drug responses due to the diversity of tendinopathy. Hence, this study attempted a classification of 126 diseased tendons into three distinct subtypes with opposite pathogenic mechanisms based on transcriptomic and clinical features. The hypoxic atrophic subtype with white appearance (Hw) exhibits downregulated neovascularization pathways. The inflammatory proliferative subtype with white appearance (Iw) shows a moderate upregulation of inflammatory characteristics. The inflammatory proliferative subtype with red appearance (Ir) exhibits the highest levels of upregulated neovascularization and inflammatory pathways, along with severe joint dysfunction. We then established research models, including subtype-specific simulations in animal models and clinical data analysis. These revealed that glucocorticoid, a controversial commonly used drug, was only effective in treating the Ir subtype. Hence, the tendinopathy subtypes elucidated in this study have significant implications for developing precision treatment of tendinopathy.